2004
DOI: 10.2307/3313015
|View full text |Cite
|
Sign up to set email alerts
|

Is the Federal Circuit Succeeding? An Empirical Assessment of Judicial Performance

Abstract: As an appellate body jurisdictionally demarcated by subject matter rather than geography, the United States Court of Appeals for the Federal Circuit occupies a unique role in the federal judiciary. This controversial institutional design has profoundly affected the jurisprudential development of legal regimes within its purview-especially in patent law, which the Federal Circuit has come to thoroughly dominate in its two decades of existence. In this Article, we assess the court's performance against its basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…8 While a high appeal or reversal rate could indicate a failure of generalist judges to appreciate the technical economic complexity underlying antitrust analysis it might also, for example, merely reflect a period of uncertainty in the law that may decrease over time or a disagreement between district court and appellate judges on the substantive merits (Wagner, 2004). 9 For example, it is difficult to conceive of an exclusively "legal" challenge to a district court decision in a merger case where the legal standard is whether the merger is likely to "substantially lessen competition," a test that has taken on almost exclusively economic meaning.…”
Section: Methodology and Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 While a high appeal or reversal rate could indicate a failure of generalist judges to appreciate the technical economic complexity underlying antitrust analysis it might also, for example, merely reflect a period of uncertainty in the law that may decrease over time or a disagreement between district court and appellate judges on the substantive merits (Wagner, 2004). 9 For example, it is difficult to conceive of an exclusively "legal" challenge to a district court decision in a merger case where the legal standard is whether the merger is likely to "substantially lessen competition," a test that has taken on almost exclusively economic meaning.…”
Section: Methodology and Caveatsmentioning
confidence: 99%
“…See, e.g. Moore (2001), Chu (2001), see also Wagner (2004). This literature generally does not control for individual judicial characteristics such as technical scientific background, though Moore (2001) finds no difference in reversal rates between Federal Circuit judges with technical backgrounds and those without.…”
Section: Introductionmentioning
confidence: 99%
“…Reflecting the relative imprecision of words in comparison to geophysical measures, scholars have found a relatively high reversal rate for claim construction rulings (Anderson & Menell 2012;Moore 2005a) and shown that even experienced patent jurists fare little better than new judges (Schwartz 2008(Schwartz , 2009. The jurisprudence of claim construction has been roundly criticized for lacking coherence (Burk & Lemley 2009a;Mullally 2007;Miller 2005;Wagner & Petherbridge 2004).…”
Section: Inherent Resource Characteristicsmentioning
confidence: 99%
“…(Polaroid Corp. v Reflecting the relative imprecision of words in comparison to geophysical measures, scholars have found a relatively high reversal rate for claim construction rulings (Anderson & Menell 2012;Moore 2005a) and shown that even experienced patent jurists fare little better than new judges (Schwartz 2008(Schwartz , 2009). The jurisprudence of claim construction has been roundly criticized for lacking coherence (Burk & Lemley 2009a;Mullally 2007;Miller 2005;Wagner & Petherbridge 2004).…”
Section: Inherent Resource Characteristicsmentioning
confidence: 99%